Global reduction in sensitivity of vegetation water use efficiency to increasing CO2 - Chai, Y; Miao, C; Berghuijs, WR; Yang, Y; Zhu, B; Hu, Y; Slater, L (Elsevier, 2024)
Ecosystem water use efficiency (WUE), which measures the ratio of carbon gain to water loss, is crucial to the global water, energy, and carbon cycles. It is an important metric in understanding how efficiently an ecosystem uses water to assimilate carbon and is affected by various environmental factors, including CO2 levels. However, the temporal dynamics of CO2-induced changes in WUE (CO2_WUE) remain uncertain. After isolating CO2_WUE from total changes in WUE, we assessed historical changes in global CO2_WUE and future projected trends. We found that the increasing atmospheric CO2 concentration enhanced global WUE by 5.65 ± 1.14 % 100 ppm−1 during 1982–2015. However, CO2-driven gains in WUE exhibit a significant declining trend across most of the Earth's land surface during 1982–2015 (−1.38 ± 0.19 % 100 ppm−1 yr−1). This widespread CO2_WUE decline is projected to continue throughout the remainder of the 21st century. The decline in CO2_WUE implies that the global land surface is likely to witness a higher water cost to maintain the land carbon sink. This finding suggests a heightened difficulty of mitigating global warming and an elevated risk of global water scarcity. The global CO2_WUE decline is primarily driven by rising vapor pressure deficit (VPD) reducing photosynthesis and increasing total evaporation. Our findings highlight the key role of VPD in the coupling of global water and carbon cycles and reveal a continuous increase in the water cost of the global land carbon sink.